Into the Woods: Revealing Ireland's Iron Age Woodlands Through Archaeological Charcoal Analysis. (3rd July 2018) - O'Donnell, Lorna
ABSTRACT: The Iron Age in Ireland (700 BC-AD 400) has long been considered an enigmatic period, with a lack of archaeological evidence for everyday settlements. Given the recent explosion of archaeological excavations in Ireland due to the boom period of the Celtic Tiger years, it has now become possible to examine many aspects of daily life during this time. Woodlands were an integral resource during prehistory and one environmental method which has been under utilised in the study of Irish woodlands is archaeological charcoal analysis. In this study, charcoal is used to reconstruct past woodland environments from the Late Bronze and Iron Age in the south of Ireland. It potentially demonstrates a shift to wetter conditions during the Developed Iron Age. The first use model for fuel during the Iron Age is produced, indicating selection of species for certain activities such as smelting, construction and cremation, while trees were not specifically selected for domestic fires. Charcoal data indicates an increase in large tree cover, mainly oak, during the 'Late Iron Age Lull'.